Teaching Aids in General Education Schools: Provision and Usage - Kalvaitis, Albinas (Pedagogika, 2015)
Lithuanian Education law establishes teachers’ right to choose the mean and form of his own pedagogical activity and teachers’ duty to ensure a good education quality. A possibility to choose and use right teaching aids – that is an important aspect of lessons’ quality. In the article the level of provision of various teaching aids and how different teaching aids are used during the lesson in general education schools in Lithuania is discussed. The analyse of the situation in these schools is based on a teachers’ survey that has been held by the author himself in 2013. In total 618 teachers, working in 221 different general education schools in Lithuania have been questioned. Results of the research show, that teaching and learning in Lithuanian general education schools are oriented to use only printed teaching aids, usually coursebooks. From all of the teaching aids the school has, teachers estimated only the amount of the coursebooks is estimated to be enough to conduct a lesson. Often Lithuanian teachers prefer to use handouts made by themselves in order to differentiate and individualize the teaching process. In conclusion the author suggests to accept and fulfil a new material provision paradigm, which would allow to create better conditions for pupils to use digital teaching aids.